Involvement of µ-opioid Receptors and κ-opioid Receptors in Itch-related Scratching Behaviour of Imiquimod-induced Psoriasis-like Dermatitis in Mice - Nobuaki Takahashi; Mitsutoshi Tominaga; Ryohei Kosaka; Yayoi Kamata; Yoshie Umehara; Hironori Matsuda; Azumi Sakaguchi; Hideoki Ogawa; Kenji Takamori (Medical Journals Sweden, 2017)
The pathogenesis of psoriatic itch is poorly understood. The aim of this study was to investigate the involvement of opioid receptors in scratching behaviour of imiquimod-induced psoriasis-like dermatitis model mice. Topical application of 5% imiquimod cream to the rostral back skin of mice induced antihistamine-resistant scratching behaviour. The expression of µ-opioid receptor (MOR) protein increased in the epidermis, dorsal root ganglia (DRG) and spinal cord of imiquimod-treated mice. In contrast, the expression of κ-opioid receptor (KOR) protein decreased in the DRG and spinal cord of imiquimod-treated mice, and was undetectable in the epidermis of both groups. Topical or intraperitoneal administration of the MOR antagonist naloxone and oral administration of the centrally acting KOR agonist ICI-199,441 inhibited scratching behaviour, whereas oral administration of the peripherally-selective KOR agonist asimadoline did not. These results suggest that peripheral and central MOR and central KOR may be involved in the modulation of scratching behaviour in imiquimod-treated mice.